ANALISA PRODUKTIVITAS TANAMAN KARET (Havea brasiliensis Muell. Arg) KLON PB 260 DENGAN MENGGUNAKAN BERBAGAI SISTEM SADAP DI AFDELING I KEBUN BANGUN PT. PERKEBUNAN NUSANTARA III - Muhammad Haiqal Fikri; Zulham Effendi; Hardy Wijaya (Agro Estate, 2022)
The productivity of rubber plantations is determined by the type of clone, the age of the plant, the level of land suitability, and the exploitation system applied. The exploitation system applied determines the productivity of the rubber plantation because it is related to the use of the skin and the physiological process of latex. Implementing the right exploitation system can ensure high and sustainable productivity. On the other hand, the implementation of the wrong exploitation system can result in low productivity and shorten the economic life of the plant. This study aims to determine the productivity of rubber plants in clone PB 260 with various tapping systems. This research was conducted at Afdeling I Kebun Bangun PT. Perkebunan Nusantara III using a descriptive analysis method by collecting secondary data on the productivity of the PB 260 clone rubber plant from 2016 – 2020. The parameters observed were the production data of the PB 260 clone rubber plant with various tapping systems. The results of this study indicate that the analysis of rubber plant productivity data in 2016 – 2020 had the highest production in 2017 with a planting year of 2009 and the lowest in 2020 with a planting year of 2000. Meanwhile, overall, the highest production was in 2018 and the lowest was in 2016. The factors that influence the high and low productivity are caused by the tapping system that is not permanent or changing, the lack of application of fertilization, the reduction in the number of trees in the field caused by being attacked by JAP (White Root Fungus), KAS (Dry Alur Sadap), Moldy Road, fallen trees due to strong winds, and the age of the plants. The relationship between production and cost of goods/kg is that the greater the production obtained, the lower the cost of goods/kg.